Penegakan Hukum Administrrasi Pengelolaan Lingkungan Hidup di Lokasi Pertambangan - La ode Munawir; La Ode Bariun; Suriani BT Tolo; Muhamad Karnoha Amir (Universitas Widya Gama Malang, 2023)
The surveillance provided by the energy service and mineral resources inspector of the southeast province of sulawesi in 2019 revealed mining operations that had not taken a good look at contamination prevention and environmental damage. Problem 1) how does the management of the environment at the mine location in northern stick 2) how does improving the management of the environment at mine location in northern stick. The purpose of research 1) to analyze the management of the environment at the mine location in northern konawe 2) to analyze the improved management of the environment at the mine location in northern konawe. The type of empirical legal research for primary data in interviews and observations supported by secondary data. The results of environmental management research have been carried out by authorities from the elements inspector of the ward service mine through the development and control of the operation of the mining operations. Through the phasing procedures, fines and penalties of the mining stops. The control and development of the 2021-2022 found two mining companies in violation of the code of mining law.